Cardiopulmonary resuscitation development. - Geddes, L.A.
As the popularity of chloroform as an anesthetic agent grew, deaths associated with its use began to be reported. It was found that this was due to respiratory and cardiac arrest. Cardiopulmonary resuscitation (CPR) is a method for restoring the circulation and respiration in a patient who has suffered cardiopulmonary arrest, often the sequel to a heart attack. The method involves forcible rhythmic chest compression to squeeze blood out of the arrested heart and mouth-to-mouth inflation of the lungs (with the nose clamped with the index finger and thumb). The method derived separately from two sources: 1) artificial respiration and 2) external chest compression to expel blood from the heart. This paper discusses studies of resuscitation associated with chloroform anesthesia.
Keywords: Artificial respiration; Blood; Cardiac arrest; Cardiopulmonary resuscitation; Chloroform anesthesia; Circulation; Forcible rhythmic chest compression; Heart attack; Mouth-to-mouth lung inflation; Respiratory arrest